Content validity index: development of learning model for basic skills of basketball passing - Herri Yusfi; Soleh Solahuddin; Syamsuramel Syamsuramel; Wahyu Indra Bayu; Destriani Destriani (Universitas Bengkulu, 2021)
Physical education teachers are required to be creative in carrying out learning, especially if there are problems with sports facilities and infrastructure in schools. The learning model must be adaptive, especially to the limited facilities and infrastructure of physical education. In addition, the implementation of physical education learning, most of which still uses the drill method, cannot be used in physical education learning, especially if the facilities and infrastructure owned are limited, because it will create boredom in students because of the time waiting for their turn to do motion tasks. This article aims to determine the value of the content validity index (CVI) from development research to create a learning model for the basic skills of basketball passing for students which are expected to be a solution to the problems. The learning model that will be developed later is a learning model using traditional play and sports approaches. CVI was developed by education experts and has been widely used in sharing research to determine the validity of the content. Three experts consisting of education, basketball, and learning experts were asked to evaluate the development of a learning model for basic basketball passing skills. The results of expert validation on the development of a learning model of basketball passing basic skills obtained i-CVI was 0.867 and the average proportion of items considered relevant in the three experts was 0.8; 0.8; and 0.93. The conclusion of this study is the production of products that are declared valid and can be continued at the trial stage using learning materials for traditional games of Orekan, bentengan games, and cat and mouse games. The implementation of this research is expected to be used by teachers in learning so that it is expected to improve basketball learning outcomes, especially the passing skills.